Relationship between carotid-femoral pulse wave velocity and decreased left ventricular diastolic function in patient with coronary heart disease: a cross-sectional study - Gu, Haojie; Liang, Guoliang; Zhang, Wenhao; Gu, Xinxin; Zhang, Qiong; Ma, Jiangwei (Frontiers in Cardiovascular Medicine, 2025)
BackgroundArterial compliance is an independent predictor of diastolic dysfunction. Invasive catheterization can accurately reflect diastolic function. However, studies on the invasive assessment of diastolic function are currently limited. This study aimed to determine whether the diastolic function of the heart can be predicted by combining noninvasive detection of arterial elasticity indicators.MethodsThis cross-sectional study included 390 hospitalized patients suspected of having coronary heart disease and underwent coronary angiography (CAG) at the South Hospital of the Sixth People's Hospital Affiliated to Shanghai Jiaotong University from June 2020 to June 2021. According to the degree of coronary artery stenosis, they were divided into group A (control, n = 73), group B (coronary stenosis < 50%; n = 128), and group C (coronary stenosis ≥ 50%; n = 189). Data of all enrolled patients, such as clinical information as well as noninvasive ultrasound and invasive cardiac catheterization results, were registered.ResultsSignificant differences in Left ventricular ejection fraction (LVEF), Ratio of peak mitral valve blood flow during early diastolic period to mitral ring velocity (E/e'), Left atrial volume index (LAVI), Deceleration time (DT), Carotid-femoral pulse wave velocity (cfPWV), Maximum velocity of left ventricular rise (LV + dp/dtmax), Maximum velocity of left ventricular descent (LV-dp/dtmax) and the left ventricular isovolumic relaxation time constant T were observed among the three groups (P < 0.01). Bivariate correlation analysis showed that cfPWV was positively correlated with T (r = 0.69, P < 0.01), E/e'(r = 0.59, P < 0.01), LAVI (r = 0.47, P < 0.01). Multiple linear regression analysis showed that cfPWV was correlated with T (r = 0.44, P < 0.01), E/e' (r = 0.24, P < 0.01), LAVI (r = 0.17, P < 0.01). Binary Logistic regression analysis showed that elevated cfPWV was associated with an increased risk of left ventricular hypodiastolic function [odds ratio (OR) = 3.30, 95% confidence interval (CI): 2.18–4.98, P < 0.01]. ROC curve analysis showed that the area under the curve of cfPWV response to diastolic dysfunction was 0.88 (95% CI: 0.85–0.91).ConclusionscfPWV is significantly associated with left ventricular diastolic dysfunction in patients with coronary heart disease, and may also be used as a sensitive indicator to predict left ventricular diastolic dysfunction.